Information System for Sales of Spare Parts at Drs. Workshop - Nugraha Sujudi; Herlinda Herlinda; Lin Suciani Astuti (bit-Tech, 2022)
Designing a Java netbeans-based sales information system for the Drs. Workshop business. The research method used is a qualitative method, which is a research method based on interviews or in-depth observations of the research subject. With the creation of a sales information system at the Drs. Workshop business based on neatbeans, all activities related to the sales data of goods can run well and smoothly. In this application, the sales data management section can handle inputting data about all sales transactions quickly and can be updated easily. This Drs. Workshop spare part sales information system is made with Netbeans and MySQL as its data base. This information system can be used to manage sales data, incoming and outgoing goods, also to perform sales calculations based on the data that has been inputted, and can be used to print reports. Finally, with this sales information system, the sales calculation process can be done automatically without the need to calculate manually and the sales data obtained are appropriate, provided that all the data entered is valid.